Expansão térmica de nanotubos de carbono de duas camadas - Guarnetti, Leandro Jose [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The special properties of carbon nanotubes (NTs) have inspired researchers in many technological applications. Examples of macroscopic products that contain or are made of CNTs are tennis rackets, baseball bats, bicycle frames, ligthweiht wind turbine blades and boat hulls. In order to get more knowledge about the behavior of these products and materials, either to develop new applications or improve the actual ones, it is important to investigate the physical properties of individual CNTs in diverse situations. In this work, using tools of molecular dynamics simulations, we present three results for the coefficient of thermal expansion of the Double Walled CNTs (DWCNTs) (5.5)@(10,10) with and without defects. The types of defects considered here are carbon atoms at interstitial sites and sp connections between the walls of the (5,5)@(10,10) DWCNT. Our methods are, first, validate by the calculation of the coefficient of thermal expansion of the Single Walled CNT (SWCNT) (10,10) and the camparison of the result with that from the literature. We show that the coefficient of thermal expansion of the (5,5)@(10,10) DWCNT. This result is discussed in terms of the coefficient of thermal expansion of the diamond

As propriedades especiais dos nanotubos de carbono (CNTs) inspiraram pesquisadores em diversas aplicações tecnológicas. Diversos produtos macroscópicos que são feitos ou contém nanotubos de carbono já existem como raquetes de tênis, tacos de beisebol, quadros de bicicletas, pás de turbinas eólicas e cascos de embarcações. A fim de de obter mais conhecimento sobre o comportamento desses produtos e materiais, seja para o desenvolvimento de novas aplicações ou melhorar as já existentes, é importante continuar investigação das propriedades físicas individuais dos nanotubos de carbono. Neste trabalho, utilizando ferramentas de simulação de dinâmica molecular, apresentamos os resultados para o coeficiente de expansão térmica de três nanotubos de carbono de duas camadas (DWCNTs Double Walled (CNTs) (5,5)@(10,10), sem e com defeitos. Os defeitos considerados nesse estudo são de dois tipos: átomos de carbono intersticial e ligações do tipo sp entre as camadas. Validamos nossos métodos calculando o coeficiente de expansão térmica do nanotubo de carbono de uma camada (SWCNT Single Walled CNT) (10,10) e comparando os resultados com os presentes na literatura. Nós mostramos que os defeitos reduzem, em módulo, o coeficiente de expansão térmica do (5,5)@(10,10) DWCNT. Discutimos esse resultado em comparação com o valor do coeficiente de expansão térmica do diamante
Thermal expansion of double walled carbon nanotubes
Keywords: Nanotubos de carbono; Dinamica molecular; Metodos de simulação; Carbon nanotubes